Bispecific sigma-1 receptor antagonism and mu-opioid receptor partial agonism: WLB-73502, an analgesic with improved efficacy and safety profile compared to strong opioids - Alba Vidal-Torres; Begoña Fernández-Pastor; Mónica García; Eva Ayet; Anna Cabot; Javier Burgueño; Xavier Monroy; Bertrand Aubel; Xavier Codony; Luz Romero; Rosalía Pascual; Maria Teresa Serafini; et al. (Elsevier, 2023)
Opioids are the most effective painkillers, but their benefit-risk balance often hinder their therapeutic use. WLB-73502 is a dual, bispecific compound that binds sigma-1 (S1R) and mu-opioid (MOR) receptors. WLB-73502 is an antagonist at the S1R. It behaved as a partial MOR agonist at the G-protein pathway and produced no/unsignificant β-arrestin-2 recruitment, thus demonstrating low intrinsic efficacy on MOR at both signalling pathways. Despite its partial MOR agonism, WLB-73502 exerted full antinociceptive efficacy, with potency superior to morphine and similar to oxycodone against nociceptive, inflammatory and osteoarthritis pain, and superior to both morphine and oxycodone against neuropathic pain. WLB-73502 crosses the blood-brain barrier and binds brain S1R and MOR to an extent consistent with its antinociceptive effect. Contrary to morphine and oxycodone, tolerance to its antinociceptive effect did not develop after repeated 4-week administration. Also, contrary to opioid comparators, WLB-73502 did not inhibit gastrointestinal transit or respiratory function in rats at doses inducing full efficacy, and it was devoid of proemetic effect (retching and vomiting) in ferrets at potentially effective doses. WLB-73502 benefits from its bivalent S1R antagonist and partial MOR agonist nature to provide an improved antinociceptive and safety profile respect to strong opioid therapy.